Moana: Representasi Pemimpin Perempuan Berkulit Hitam - Farida Jaeka (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2020)
This research aims to analyze the character of Moana in the animated film, Moana (2016), as a representation of black female leaders. The animated film is produced by Walt Disney, USA. In addition, the interesting thing about the film is the attitude of leadership which is shown by the character Moana. Stories emphasized primarily in the struggle of ‘black women’ –which is often considered as a “liyan” in the United States— inrestoring the welfare of her community. This research uses the qualitative method and analyzed by the feminist literary criticism. From the three waves of feminism, which were shared by Cudd and Andreasen, Moana belongs to the third group—the wave that no longer sues the patriarchy, but rather to present a figure of a strong and courageous woman. The result of this research is Moana succeeded to show the leadership attitude of a black woman. She also succeeded to restore the welfare of Mautunui villagers by restoring the heart of TeFiti—theisland goddess. Her attitude as a leader is shown in her efforts to restore the heart, which has fought against the invasion of a coconut monster, facing Crab in Lalotai—themonster world, and facing TeKa-The lava monster. The film is used as a medium to state and represents that in terms of leadership, men’s and women’s rights are equal—eventhough they are white or black.